PENGARUH GIVEAWAY TIKET KONSER BLACKPINK OLEH GERINDRA DAN PSI TERHADAP PERILAKU MEMILIH K POPERS PADA PEMILU 2024 - Shasa Nabila; Kushandajani Kushandajani (Journal of Politic and Government Studies, 2026)
The phenomenon of K-Pop popular culture is now being utilized as a political communication strategy in Indonesia, one of which is through the Giveaway of Blackpink concert tickets by the Gerindra Party and PSI ahead of the 2024 Election. This study aims to analyze the influence of this activity on the voting behavior of K-Popers through sociological, psychological, and rational approaches within voter behavior theory. The research uses a quantitative method with a questionnaire administered to 100 K-Popers respondents, and the data were analyzed using descriptive statistics and simple linear regression. The results show that the Giveaway is able to attract attention and spark discussion within the community, but is not sufficient to shape a tendency toward political support. Sociologically, the K-Pop community becomes a space for forming critical attitudes toward the politicization of popular culture. Psychologically, this strategy does not create emotional closeness with the party. From a rational perspective, the Giveaway is considered attractive but does not influence political preferences. Thus, political strategies based on popular culture are effective only in increasing public attention, but have not been able to shift the political orientation of K-Popers without the support of more relevant programs.